Meningkatan Hasil Belajar Lempar Tangkap Bola Melalui Permainan Letabotai (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the increase of learning outcomes through the game throwing the ball catching letabotai the first-grade students of SDN 03 Pagojengan District of Paguyangan Brebes. This study uses the results of the analysis of action research class.Berdasarkan percentage per cycle, learning through games throwing a ball catching letabotai have a positive impact on improving student learning outcomes characterized by increased mastery learning students in each cycle of the first cycle fulfilled Affective Value 62.50%, the second cycle is met 95.00%. Value cognitive cycle I fulfilled 55.00%, 90.00% second cycle. Psychomotor value of the first cycle is met 10.00%, 92.50% second cycle.